Handbook of research on deep learning innovations and trends - Hassanien, Aboul Ella; Darwish, Ashraf; Chowdhary, Chiranji Lal 1975- (IGI Global, 2019)
"This book explores the application of deep learning in various areas like computer vision, image processing, biometrics, pattern recognition and medical imaging, and other real-world applications"--